The Scolopendra species (Chilopoda: Scolopendromorpha: Scolopendridae) of Greece (E-Mediterranean): a theoretical approach on the effect of geography and palaeogeography on their distribution - Simaiakis, Stylianos; Mylonas, Moisis (Zootaxa, 2008)
The species of the genus Scolopendra Linnaeus, 1758 are very widely distributed in the Mediterranean region. Current knowledge is summarized, with references to material derived mainly from the well-explored islands of the Aegean Archipelago, several localities in continental Greece and old bibliographic reports. We suggest that Scolopendra species represent examples of both paradigms of historical biogeography, namely vicariance and dispersal. We propose that the dispersal routes of Scolopendra species in Greece were mainly influenced by late Miocene and upper Pleistocene palaeogeography. The formation of the Mid-Aegean trench (c. 12 – 9 Mya) considered as a remarkable geographical barrier between the Anatolian peninsula and mainland Greece, prevented the entry of certain Scolopendra species westwards. In total, five Scolopendra species have been recorded from mainland and insular Greece. A vicariance event that occurred in the area more than 17 Mya, when the Aegean region was part of a united landmass, better explains the biogeographical history of S. canidens. Cyclades harbours remnants of the ancient populations of S. canidens, whereas during the late Pleistocene (c. 400.000 21.000 ya) S. canidens was isolated in Dodecanese. S. cretica is the only endemic, being distributed in Crete and its adjacent islets. S. clavipes in E-Mediterranean and S. dalmatica in W-Mediterranean evolved from ancient canidens populations. S. cingulata entered central and southern Europe from the east (c. 20 – 11 Mya), while the formation of the Mid-Aegean trench (c. 12 – 9 Mya) prevented its entry in Crete.